1999
DOI: 10.1103/physrevb.59.11159
|View full text |Cite
|
Sign up to set email alerts
|

Intergrain tunneling magnetoresistance in polycrystals of the ordered double perovskiteSr2FeReO6

Abstract: Intergrain tunneling magnetoresistance ͑TMR͒ subsisting up to room temperature has been observed for polycrystalline ceramics of Sr 2 FeReO 6 , which has ordered double perovskite structure with Curie temperature above 400 K. The first-principles band calculation predicts that Sr 2 FeReO 6 shows the half metallic ground state with the ferrimagnetic coupling of Fe and Re spins. The experimental results of electronic and magnetic properties are in accord with this picture. In fact, the magnitude of intergrain TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
278
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(294 citation statements)
references
References 11 publications
9
278
0
Order By: Relevance
“…A similar behaviour is seen in Figure 2 of Ref. [22] for an SFRO sample sintered in an Ar atmosphere. Prolonged heat treatment of our sample in air at 400 o C restored inter-grain tunnelling and the σ(T) plot straightened up (see lower curve in Fig.…”
Section: Resultssupporting
confidence: 63%
“…A similar behaviour is seen in Figure 2 of Ref. [22] for an SFRO sample sintered in an Ar atmosphere. Prolonged heat treatment of our sample in air at 400 o C restored inter-grain tunnelling and the σ(T) plot straightened up (see lower curve in Fig.…”
Section: Resultssupporting
confidence: 63%
“…7 Although Sr 2 FeReO 6 (see Ref. 8) shows similar TMR properties to those of Sr 2 FeMoO 6 , recent studies claim that the Ca-compound, Ca 2 FeReO 6 , unlike Ca 2 FeMoO 6 , may be insulating. 9 It has been suggested that the magnetic temperature T c , and whether the ground state is metallic or insulating, vary as A is changed from Ba to Sr to Ca.…”
Section: Introductionmentioning
confidence: 99%
“…T C = 635 K in Sr 2 CrReO 6 [2]. Large low field magnetoresistance effects are found in Sr 2 FeMoO 6 [1,3], Sr 2 FeReO 6 [4] and Sr 2 CrWO 6 [5]. Thin films of the well studied system Sr 2 FeMoO 6 have been fabricated by pulsed-laser deposition (PLD) at relatively high temperatures of about 900 • C [6].…”
mentioning
confidence: 99%